Treatment of dyslipidemia in the elderly - Shao, Hong; Chen, Li-Quan; Xu, Jun (Journal of geriatric cardiology : JGC, 2011)
Dyshpidemia is a well-established risk factor for atherosclerosis. Treating dyslipidemia in elderly patients requires specific knowledge and understanding of common dyslipidemias and the relative safety of various pharmacologic agents in the presence of possible multiple comorbidities. Lifestyle modification remains the first step in the treatment of dyslipidemia; however, it can be difficult to sustain and achieve acceptable compliance in the elderly and it is best used in combination with drug therapy. Statins are widely accepted as the first-line therapy. Several recent studies have demonstrated that statins are safe and effective in the elderly. However, it is important to note that there is very limited data regarding the effects of dyslipidemia treatment on morbidity and mortality in patients over 85 years of age. In summary, the clinicians must recognize that the presence of dyslipidemia in the elderly poses substantial risk of coronary events and stroke. The available evidence has demonstrated that in most elderly patients who are at increased risk for cardiovascular morbidity and mortality, treatment of dyslipidemia with appropriate therapy reduces the risk, and when used carefully with close monitoring for safety, the treatment is generally well tolerated. With increasing life expectancy, it is critical for physicians to recognize the importance of detection and treatment of dyslipidemia in the elderly.